Effects of varying the amount of reduced graphene oxide loading on the humidity sensing performance of zinc oxide/reduced graphene oxide nanocomposites on cellulose filter paper - Mamat, Mohamad Hafiz; A Subki, A Shamsul Rahimi; Musa, Mohamed Zahidi; Abdullah, Mohd Hanapiah; Shameem Banu, Itreesh Basha; N. Vasimalai; Ahmad, Mohd Khairul; Nayan, Nafarizal; Abu Bakar, Suriani; Azmi, Mohamed; M. Danang, Birowosuto; Mahmood, Mohamad Rusop (Elsevier Ltd, 2022)
This work presents a nanocomposite-based humidity sensor based on zinc oxide nanostructured powder (ZNP) nanoparticles that achieves a maximum enhancement in the humidity sensing performance at room temperature due to the introduction of different amounts of reduced graphene oxide (rGO) loading from 0.5 wt% to 2.0 wt%. The rGO/ZNP (rZNP) nanocomposite-based humidity sensor was fabricated by using cellulose filter paper as a substrate and clear paper glue as a binder through a facile brush printing method. FESEM, EDS, XRD, HRTEM, XPS, and Raman spectroscopy were employed to investigate the properties of the ZNP and rZNP nanocomposites. The presence of an rZNP nanocomposite with quasi-spherical ZNP nanoparticles that are securely attached and anchored with rGO sheets was confirmed through HRTEM micrographs. Raman spectroscopy analyses confirm and validate the formation of hybrid nanostructures with the presence of distinctive bands related to ZNP and rGO. The presence of oxygen vacancy defects and oxygen-related chemical bonds on the surface of the rZNP nanocomposite, which yields enhanced sensor performance, is revealed by XPS analysis. The rZNP nanocomposite-based humidity sensor with 1.0 wt% rGO loading (rZNP-1.0) had a maximum sensing response of 99.42% and exhibited the highest sensitivity towards humidity changes (172 or 29.2 MΩ/%RH), which was substantially better than the other tested samples.